2017
DOI: 10.1021/acs.jmedchem.7b01154
|View full text |Cite
|
Sign up to set email alerts
|

Small-Molecule Inhibitors of the CD40–CD40L Costimulatory Protein–Protein Interaction

Abstract: Costimulatory interactions are required for T cell activation and development of an effective immune response; hence, they are valuable therapeutic targets for immunomodulation. However, they, as all other protein-protein interactions, are difficult to target by small molecules. Here, we report the identification of novel small-molecule inhibitors of the CD40–CD40L interaction designed starting from the chemical space of organic dyes. For the most promising compounds such as DRI-C21045, activity (IC50) in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(80 citation statements)
references
References 115 publications
(287 reference statements)
4
75
1
Order By: Relevance
“…thromboembolic complications have been developed. These reagents include PEG-conjugated antibodies [44,45] and immunomodulatory small molecules targeting the CD40L [46][47][48].…”
Section: Targeting Immune Checkpointsmentioning
confidence: 99%
“…thromboembolic complications have been developed. These reagents include PEG-conjugated antibodies [44,45] and immunomodulatory small molecules targeting the CD40L [46][47][48].…”
Section: Targeting Immune Checkpointsmentioning
confidence: 99%
“…Accordingly, it seemed logical to explore it for possible inhibitors of the SARS-CoV-2 S protein -ACE2 PPI that is an essential first step for the viral entry of this novel, highly infectious coronavirus. As a first step, we explored the feasibility of setting up a screening assays using a cell-free ELISA-type 96-well format similar to those used in our previous works with Fc-conjugated receptors coated on the plate and FLAG-or His-tagged ligands in the solution (Margolles-Clark et al, 2009b;Ganesan et al, 2011;Song et al, 2014;Chen et al, 2017). To establish assay conditions, we first performed concentration-response assessments using such a format with ACE2-Fc and SARS-CoV-2 S1 or RBD with His tag, and they indicated that both bindings follow classic sigmoid patterns with a slightly stronger binding for RBD than S1 (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Binding inhibition assays were performed in a 96-well cell-free format similar to the one described before (Margolles-Clark et al, 2009b;Ganesan et al, 2011;Song et al, 2014;Chen et al, 2017). Briefly, microtiter plates (Nunc F Maxisorp, 96-well; Thermo Fisher Scientific, Waltham, MA, USA) were coated overnight at 4 °C with 100 μL/well of Fc-conjugated ACE2 receptor diluted in PBS pH 7.2.…”
Section: Binding Assaysmentioning
confidence: 99%
See 2 more Smart Citations